Study of body image in professional dancers: A systematic review EStudo da imagem corporal em bailarinos profissionais: Uma revisão sistemática Estudio de la imagen corporal en bailarines profesionales: Una revisión sistemática - Cardoso A.A.* (2017)
© 2017, Redprint Editora Ltda. All rights reserved.Body image is multidimensional, dynamic, and entirely linked to the body in motion, which entails relevant bodily concerns in the routine of professional dancers, who need to maintain their body aesthetics constantly. The objective was summarizing the scientific production on the body image of professional dancers and to understand how they perceive it. This review is composed by seven studies that investigated professional dancers of classical ballet, jazz and contemporary dance. The results demonstrate that even though they are lean and had appropriate body mass index, professional dancers are dissatisfied with their body and wish to be thinner, that is, professional dancers constitute a risk group for the development of eating disorders.